2007
DOI: 10.1534/genetics.106.067488
|View full text |Cite
|
Sign up to set email alerts
|

The Nonmuscle Myosin Phosphatase PP1β (flapwing) Negatively Regulates Jun N-Terminal Kinase in Wing Imaginal Discs of Drosophila

Abstract: Drosophila flapwing ( flw) codes for serine/threonine protein phosphatase type 1b (PP1b). Regulation of nonmuscle myosin activity is the single essential flw function that is nonredundant with the three closely related PP1a genes. Flw is thought to dephosphorylate the nonmuscle myosin regulatory light chain, Spaghetti Squash (Sqh); this inactivates the nonmuscle myosin heavy chain, Zipper (Zip). Thus, strong flw mutants lead to hyperphosphorylation of Sqh and hyperactivation of nonmuscle myosin activity. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…Expression of the constitutively active Sqh EE (Jordan and Karess, 1997; Kirchner et al, 2007), is sufficient for apical constriction and invagination in the wing imaginal epithelium (Fig. 7C–C”, D), but the clones are not round like APC null clones (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of the constitutively active Sqh EE (Jordan and Karess, 1997; Kirchner et al, 2007), is sufficient for apical constriction and invagination in the wing imaginal epithelium (Fig. 7C–C”, D), but the clones are not round like APC null clones (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with a role for active MyoII in APC null apical constriction, the doubly phosphorylated form of Sqh, but not total Sqh or singly phosphorylated Sqh, was enriched in apically constricting APC null cells (Zimmerman and McCartney, unpublished observations). Expression of a mutant form of Sqh in which both Ser-21 and Thr-20 have been replaced by alanines (Sqh AA ) (Jordan and Karess, 1997; Kirchner et al, 2007) in APC null cells suppressed apical constriction (Fig. 7F, G, H).…”
Section: Resultsmentioning
confidence: 99%
“…Another study revealed that overexpression of wild-type Rho1 in the anterior-posterior boundary of the developing wing epithelium resulted in JNK-mediated apoptosis (Vidal et al, 2006). Myosin II activity has also been linked to JNK activation in a study of the Drosophila non-muscle myosin phosphatase PP1β (Flapwing), which negatively regulates JNK activity through the inhibition of Myosin II activity in the developing wing (Kirchner et al, 2007). Furthermore, a recent study has shown that depletion of the Sds22/PP1 phosphatase can cooperate with Ras ACT , via upregulation of Myosin II activity and JNK activation (Jiang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that not all sds22 deficient cells induce active JNK indicates that sds22/PP1 may regulate JNK activity indirectly through regulation of upstream components. Genetic studies suggest that Drosophila PP1β can regulate JNK through myosin II (Kirchner et al , 2007b). However, blocking myosin II activity in our study does not abolish the sds22/PP1 -mediated JNK activation (data not shown).…”
Section: Discussionmentioning
confidence: 99%